DETERMINAN PENCEGAHAN FRAUD PENGELOLAAN KEUANGAN DESA DI KABUPATEN ACEH TIMUR - Nadiatul Aqsa; Afrah Junita; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This research aims to determine the influence of apparatus competency, integrity and accountability on preventing fraud in village financial management partially and simultaneously. This type of research uses quantitative research, the data source for this research uses primary data. The population and sample for this research are villages in the Peudawa sub-district, totaling 17 villages as the population and the sample taken in this research was 60 village officials. The data obtained was analyzed using SPSS analysis techniques. The equation model analyzed is multiple linear regression analysis, classical assumption testing and hypothesis testing (T test, F test and Coefficient of Determination (R2)). The partial research results show that the competence of village officials has a positive and significant effect on preventing fraud in village financial management, integrity has a positive and significant effect on preventing fraud in village financial management, accountability has no effect on preventing fraud in village financial management. Simultaneous research results show that together village apparatus competency, integrity and accountability have a positive and significant effect on preventing fraud in village financial management. with a termination coefficient (R2) of 70.1%, it influences the prevention of fraud in village financial management, while 29.9% is influenced by other variables outside the research. The limitation of this research is that it only used 68 respondents, which is actually not enough to describe the actual situation and the number of independent variables used is not comprehensive enough, so for further research it is hoped to add other independent variables that can influence fraud prevention in village financial management. Such as transparency, internal control systems, individual morality, whistleblowing systems and others.